A Novel Approach for Implant Rehabilitation Combined with Immediate Bone and Soft-Tissue Augmentation in a Compromised Socket—A B2S Approach: Case Report with a 2-Year Follow-Up - Baruch S. Bernatskiy; Algirdas Puišys (Case Reports in Dentistry)
In this case report, we aimed to describe a novel approach for aesthetic rehabilitation of the anterior maxilla that combined immediate implant installation with the “Bone2Soft Tissue Reconstruction” (B2S technique), which involves the use of a triple graft harvested from the maxillary tuberosity. The regeneration potential of a tuberosity graft appeared to surpass that of corticocancellous bone grafts harvested from other intraoral donor sites and allowed for quicker regeneration of both bone and soft tissue. The B2S technique extended the indications for immediate implant placement and ridge augmentation to cases involving severe bone resorption and other complex clinical scenarios. Owing to the good visualization facilitated by open-flap access, the surgical procedures can be completed in a single intervention, which will be beneficial for both doctors and patients.